Both management practices and landscape influence plant communities in urban grasslands - Gros, Clément; Bulot, Adeline; Aviron, Stéphanie; Beaujouan, Véronique; Daniel, Hervé (Frontiers in Ecology and Evolution, 2023)
The development of urban areas now requires the integration of biodiversity issues, and this leads to better consideration of their semi-natural habitats. Among these habitats, urban grasslands submitted to mowing management practices are commonly promoted over lawns to enhance biodiversity in cities. Despite their ecological value, relatively little attention has been paid to the effects of urban grassland management regimes or of the landscape contexts of these habitats in terms of biodiversity. This study aims to investigate the effects of mowing practices and the landscape context of urban grasslands on species diversity and composition and the ecological strategies of plant communities. In this study, 66 sites (mown grasslands) were selected in the Angers and Rennes conurbations of western France according to their management practices (regarding mowing) and landscape gradient (more or less urbanized).The results show that mowing practices and landscape composition did not affect the richness or diversity of plant species, but significantly influenced the composition of communities.Partitioning analysis showed that landscape composition explained twice as much of the variance of plant species composition than mowing practices did. Landscape composition favors plant species according to their strategies, preferential habitats and their life spans. Furthermore, diversification of management practices limits the establishment of non-native species and induces a wider range of functional strategies, as late mowing favors competitors and disfavors stress tolerant species. Nevertheless, management practices need to be put into perspective in the context of urban grasslands. Thus, this research brings new perspectives to recommendations for the management of urban green spaces.